(untitled) (Veterinary Science, 2017)
Healing activities of provoked wounded mice was recorded as consequence of the application of extract of Cichorium intybus, a complex family plant that growth naturally in pampas area. The Treatment group was treated topically with diluted extract for 10 days and samples were taken every day for histological analyses. In order to compare the evolution of the wounds the same procedure was applied to a nontreatment group of animals (Control group). Mice from the treated group showed a significant delay in the healing wound process (p0,05) evidenced by an increase in neutrophil and fibroblast stay in the injured tissue, as well as in the collagen fibre arrangement in relation to the control group. Under the condition of the present study the extract of Cichorium intybus did not showed healing activity.